The role of arginase in endothelial dysfunction - Rudolf Lucas (Frontiers Research Topics, 2015)
In recent years, an increasing number of manuscripts have been published addressing the deleterious role of arginase in endothelial dysfunction. ROS have been shown to play a crucial role in arginase activation, which in turn leads to eNOS dysfunction.